Endodontic treatment in tooth with pulp necrosis and periapical lesion with Reciproc Blue and XP-Endo Finisher instruments: case report (Research, Society and Development, 2021)
The objective of the endodontic treatment is to prevento r eliminate apical periodontitis by means of cleaning, shaping and filling the root canals. Chemomechanical preparation is recognized as one of the most important step for microbial reduction within the root canals. In order to overcome anatomical challenges, especially in cases of curvatures, novel heat treatments to endodontic instrument alloys have been proposed to increase its flexibility. The aim of the present clinical case report is to describe the endodontic procedures performed with Reciproc Blue and XP-Endo Finisher files in an upper lateral incisor with pulp necrosis and presence of periapical lesion. Male patient was referred to the Postgraduate Clinic of the Piracicaba Dental School - UNICAMP seeking endodontic treatment. The clinical examination revealed negative response to the pulp sensitivity cold testing. Radiographically, the presence of restoration on the mesial surface and the presence of periapical lesion were observed. Endodontic treatment was undertaken under magnification by using an operating microscope. After local anesthesia and cavity access, endodontic treatment was performed using Reciproc Blue instruments, with the crown-down technique. Patency and foraminal enlargement were performed. The instrumentation level was determined at 1 mm beyond the apical foramen. 2% chlorhexidine gel was used as auxiliary chemical substance and sterile saline solution as an irrigating solution. At the end of the chemical-mechanical preparation, final rinse was performed with 3mL of 17% EDTA, under agitation with the XP-Endo Finisher instrument for 1 minute. Then, the root canal was filled using the single cone technique using medium gutta-percha and endodontic cement (Endomethasone). The gutta-percha cut was performed with a thermoplasticizer instrument, 2 mm below the cementoenamel junction. Coronary sealing was performed by placing coltosol at the entrance of the root canals, followed by the insertion of light-curing composite resin using the incremental technique.